SEMANTIC ROLES OF PHONEMIC ELEMENTS AND SPEECH SOUNDS IN LANGUAGE STRUCTURE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the semantic functions of speech sounds and phonemes, examining their crucial role in human language. Phonemes, the smallest units of sound, distinguish words and contribute to the formation of meaning within language. The article explains how phonemic contrasts, alternations, and morphemes shape the semantics of speech. It also highlights the importance of allophones, prosody, and phonemic changes over time in influencing meaning. By detailing the interplay between phonemes and meaning, the article underscores the fundamental role these sounds play in communication, illustrating their importance not only in language structure but in conveying nuanced, complex ideas. This discussion emphasizes the dynamic and evolving nature of language, making clear the significance of phonemes in both the development and the understanding of human communication.